Long-term storage stability of incorporated hydrotreated vegetable oil (HVO) in biodiesel-diesel blends at highland and coastal areas - Nur Allif Fathurrahman; Kemal Ginanjar; Rossy Dwi Devitasari; Mamay Maslahat; Riesta Anggarani; Lies Aisyah; Ariana Soemanto; Maharani Dewi Solikhah; Arfie Thahar; Edi Wibowo; Cahyo Setyo Wibowo (Fuel Communications, 2024)
This paper reports an investigation on the long-term storage stability of high percentage and reformulated biodiesel-diesel blends for the success of renewable energy initiatives. This study mainly focuses on the Indonesian context, where the mandated B30 biodiesel faces stability and hygroscopicity challenges. A novel approach incorporated hydrotreated vegetable oil (HVO) to mitigate instability while increasing the biodiesel percentage and was analyzed during storage stability over six months in highland and coastal areas. A comprehensive analysis evaluates physicochemical properties, including water content, kinematic viscosity, total acid number, oxidation stability, and microbial growth. Based on the results, biodiesel-diesel blends (B30, B40, and B30D10) revealed robust stability and quality under highland and coastal conditions. Acid numbers exhibited a slight upward trend during storage but stayed within specified limits, emphasizing limited oxidative changes. Oxidation stability surpassed standard limits for blends, highlighting the blends' resistance to oxidation, even in higher concentrations. Water content increased over time, reflecting biodiesel's hygroscopic nature, but all blends met diesel fuel standards after 6 months. Furthermore, the investigation provided valuable insights into biodiesel-diesel blends' stability, quality, and potential enhancements, contributing to informed decision-making in fuel formulation and quality control.